Equipamento de coluna para ensaio de condutividade hidráulica de longa duração com aplicação de carga vertical - Santos, Valter Caetano dos (2013)
This study aimed to design, build, and validate a fully instrumented modified column apparatus for application in studies of hydraulic conductivity in compacted soils percolated by acidic contaminants and subjected to the action of vertical static loadings, simulating the hydraulic behavior of impermeable bottom barriers in industrial waste landfills and mining tailings dams. The development of the apparatus followed the steps: conceptual design, listing of the needed parts, preparation of technical drawings for contracting machining services, specification of mechanical, hydraulic, and pneumatic systems, software programming for data aquisition, and calibration of electronic sensors. The validation of the apparatus and its instrumentation was performed by conducting a pilot test in a compacted clayey soil. During this test, a vertical static load of 280 kPa was applied to simulate an overload of waste or tailings over the barrier. The test consisted of distilled water percolation through the specimen until it reached a condition close to saturation, followed by leaching a contaminant acidic solution of pH 1. The results confirmed the efficiency of the sensors data acquisition, which showed proper operation, as well as all hydraulic and pneumatic connections, which presented no technical failures or leaks. The pilot study indicated a relatively high coefficient of hydraulic conductivity, ranging between 1,0 x10-7 m/s and 4,6 x10-7 m/s. This value might be explained by a possible preferential flow in the interface between the acrylic chamber wall and the soil specimen